Muckenhoupt–Wheeden theorem for generalized f-Riesz-type potentials - Knopova, V. (Український математичний журнал, 2008)
We obtain the Muckenhoupt-Wheeden theorem for some class of potentials. As a consequence, we
describe the equivalent norm in the generalized Bessel potential space of negative order. Одержано теорему Макенхаупта–Відена для одного класу потенціалів. Як наслідок, описано еквівалентну норму в просторі узагальнених потенціалів Весселя від'ємного порядку.